Green marketing in Singapore. - Cheng, Liang Qi. (2011)
This report employs the STP framework (Segmentation, Targeting and Positioning) to segment the green market in Singapore, and develop strategies to enhance green consumerism among University students. It involves examining the environmental attitudes and behaviors of University students and further dividing the University population into three distinct groups, namely the Friendly, Neutral and Unfriendly, according to their level of environmentalism. A suitable marketing mix based on the 4Ps (product, price, place and promotion) was subsequently crafted for green companies or organizations to effectively target the different consumer groups. Our findings on Friendly consumers concur with existing literature, whereas the two other groups of consumers have not previously been specifically defined. Our research provided an in-depth analysis and understanding with regards to identifying and targeting of the Neutral and Unfriendly groups. Based on our findings, a focus on beauty and personal care products was recommended for the Friendly group; gender-neutral products for the Neutral group and male-oriented, sporting products for the Unfriendly group. The information derived from this study can entirely modify the focus, the target market and the marketing strategies of existing companies that produce environmentally-friendly products. Finally, the report highlights the limitations of the study due to sampling bias and data collected on a cross-sectional time basis. Further research is warranted to address these limitations, as well as to expand the investigation to the general population in Singapore.